Penerapan Mesin Pencetak Pelet Untuk Pakan Ternak Di Desa Sambigede Pakisaji Malang - Muhammad Alfian Mizar; Moch. Sholihul Hadi; Muchammad Harly (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Sambigede Village, District. Pakisaji is one of the areas that has high potential in the livestock sector in Malang Regency, the potential is around 20 thousand poultry, 100 cattle, and there are also 3 fish farming groups. So far, the animal feed pellets given by breeders are natural feed in the form of bran and other grains. Animal feed pellets, which are often referred to as pellets, are one of the most important things to pay attention to in the livestock industry, Pellets are a source of nutrition that has a huge impact on livestock, especially poultry breeders, but breeders in this village still have difficulty producing pellets because limited knowledge and technology. So it is necessary to implement an animal feed pellet printing technology machine to provide animal feed pellets in the form of feed pellets independently. The aim of this community service is to diffuse Appropriate Technology for animal feed pellet printing machines by providing knowledge and skills about how to make feed pellet products, and operation and maintenance of animal feed pellet printing machines to partners. Based on the implementation that has been carried out, production increases can be actualized to increase the production of feed pellets 40 kg/hour, so that the implementation of an animal feed pellet printing machine can provide a relatively large contribution to increasing productivity, quality, and turnover for community groups in Sambigede Village, Pakisaji, Malang.. Kata Kunci: pellet machine, pellet press machine, appropriate technology